Assessing Beaches’ Landscape and Environment in Tourism Destinations: The Case of Sithonia, Greece - Antonios, Terzidis; Dimitra, Vagiona G (Journal of Tourism Management Research, 2022)
In recent decades, the tourism industry has played an increasingly important role in countries’ national economies, although, at the same time, a lack of necessary actions has contributed to the environmental and socioeconomic degradation of several travel destinations. Nevertheless, sustainable development is achievable through planning, preventive measures, and indicators. This study aimed to assess the coastal scenery of (38) selected Tourist Beaches (TBs) in the Municipality of Sithonia, Greece, by applying an indicator-based methodology, which evaluated 21 physical and 10 human parameters. For the analysis of the landscape of TBs, a system of indicators was applied, which consisted of modified indicators of the Coastal Scenery Evaluation System (CSES) method, as well as novel proposed indicators that focused on factors that indirectly influence the coastal environment. A Questionnaire Survey (QS) was performed to assess the importance of each Assessment Indicator (AI) based on locals’ and tourists’ opinions. The Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method was then applied to rank the coastal scenery of the selected beaches in the study area, and three different classification maps were created based on the combined preferences of the participants in the QS, both locals and tourists. According to the results, the Porto Koufo and Koutloumousiou beaches obtained the highest scores in all three groups based on their important natural characteristics. Numerous TBs received high scores as tourism activity had not significantly affected their physical and anthropogenic environment.